Drug compatibility with various closed intravenous infusion containers - Zhu, Chang-yu; Zuo, Hui-ying; Li, Hong-lin; Tong, Rong-sheng (Frontiers in Pharmacology, 2024)
The aim was to systematically compare the drug compatibility with various closed intravenous (i.v.) infusion containers, to provide a reference for selecting a relatively superior infusion container and improve the medication safety for patients in clinical practice.The compatibility of four commonly used clinical injections (ceftazidime, pantoprazole sodium, ambroxol hydrochloride, edaravone) with three representative closed i.v. infusion containers (non-PVC infusion bags, upright polypropylene infusion bags, inner sealed polypropylene infusion bags) prefilled with infusion fluids (0.9% sodium chloride or 5% dextrose) in the Chinese market were investigated in this study. The particle counts of both infusion fluids and diluted chemical injections by infusion fluids in various infusion containers were determined by the light obscuration method. At 0, 2 & 6 hours after four injections following dilution with infusion fluids in each container, the pH of the solutions was detected, and the physical properties were examined by visual inspection. Meanwhile, the drug concentrations were assessed by high performance liquid chromatography (HPLC).As for either infusion fluids or diluted injections by infusion fluids, the particle counts in non-PVC infusion bags were significantly greater than those in the other two bags under some circumstances. The particle counts in diluted injections by infusion fluids increased dramatically compared with those in infusion fluids in all infusion containers, especially for the small-size particles. But pH, physical properties and drug concentrations of diluted infusion solutions in all infusion containers remained nearly unchanged over the test period.Conclusion: Closed i.v. infusion containers included in this study are all well-compatible with four injections. Moreover, the closed infusion containers produced by Chinese manufacturers have met the international quality standard. Particularly, the intravenous admixture preparation process needs to be optimized to reduce the overall particulate contaminants.